Incidencia de los riesgos físicos y mecánicos en la seguridad y salud ocupacional de los trabajadores de la planta avipechichal .S.A.,Junín - Cedeño Ferrín, Dany Antonio (2016)
The investigation determined the incidence of physical and mechanical hazards in occupational safety and health of workers AVIPECHICHAL S.A., Junin plant. Process activities were determined. Poultry has 11 activities: Quality Control, Microingredients grameados, Macroingredients, Console, Purchasing Department, Human Talent, Bagging, Molino, pelletizer, pelletizing and equipment Shale gas extraction. Workers at the plant mentioned in the random survey, they know about the risks they are exposed, use appropriate PPE, and there are rotating work schedules, among others. Monitoring lighting, vibration and noise are within the permissible limits of the applicable law (law management environment and labor) with the exception of noise in the area of production and / or Pelletizing exceeding decibel under the legislation, because the process are contiguous. Triple matrix approach, together with the method of William Fine 1971, estimated the number of moderate risk (16), major (24) and intolerable (9) of the plant. William Fine methodology he considered that the physical and mechanical hazards have a degree of danger and impact of low level. These estimates and assessed risks support the development of a manual to minimize and / or prevent physical and mechanical risks of greater importance (noise and vibration), as proposed for the continuous improvement of it.